Analysis of Greenwashing Policy in Providing Consumer Protection in Indonesia in View of Law Number 8 of 1999 Concerning Consumer Protection - Istanti, Aura Ning; Samsul, Inosentius (Universitas Muhammadiyah Sumatera Utara, 2023)
Greenwashing is a marketing strategy in which business actors sell the condition of their products as being environmentally friendly and supporting environmental conservation activities. As a result, it is necessary to conduct research using normative juridical research methods with a statutory and case approach to determine the impact of greenwashing actions carried out by business actors on consumers, as well as the government's efforts with the greenwashing method. The results of the study show that if consumers feel cheated by producers and/or companies producing goods and/or services for providing misleading information, then there will be a consumer confusion effect that occurs when a company makes a green claim, which in fact is only used as a marketing strategy alone. The impact that occurs on the environment will also damage the environment because the use of production materials will endanger environmental safety in the future and have an impact on the health of consumers themselves. In its efforts, the government has issued a policy regarding product manufacturing standards that are considered to have safe limits for consumers and the environment